Genetic assignment of recruits reveals short‐ and long‐distance larval dispersal in Pocillopora damicornis on the Great Barrier Reef. Issue 23 (8th November 2013) - Torda, G.; Lundgren, P.; Willis, B. L.; van, M. J. H.
Abstract Understanding connectivity of coral populations among and within reefs over ecologically significant timescales is essential for developing evidence‐based management strategies, including the design of marineprotected areas. Here, we present the first assessment of contemporary connectivity among populations of two Molecular Operational Taxonomic Units (MOTUs) of the brooding coral Pocillopora damicornis. We used individual‐based genetic assignment methods to identify the proportions of philopatric and migrant larval recruits, settling over 12 months at sites around Lizard Island (northern Great Barrier Reef [GBR]) and over 24 months at sites around the Palms Islands (central GBR). Overall, we found spatially and temporally variable rates of self‐recruitment and dispersal, demonstrating the importance of variation in local physical characteristics in driving dispersal processes. Recruitment patterns and inferred dispersal distances differed between the two P. damicornis MOTUs, with type α recruits exhibiting predominantly philopatric recruitment, while the majority of type β recruits were either migrants from identified putative source populations or assumed migrants based on genetic exclusion from all known populations. While P. damicornis invests much energy into brooding clonal larvae, we found that only 15% and 7% of type α and type β recruits, respectively, were clones of sampled adult colonies or other recruits, challenging the hypothesis that reproduction is predominantly asexual in this species on the GBR. We explain high rates of self‐recruitment and low rates of clonality in these MOTUs by suggesting that locally retained larvae originate predominantly from spawned gametes, while brooded larvae are mainly vagabonds.